Zoonotic threat of cystic echinococcosis in Tunisia: insights into livestock prevalence and identification of the G1 genotype - Abdelghani, Mohamed Hedi; M’rad, Selim; Chaâbane-Banaoues, Raja; Taoufik, Sayadi; Charfedine, Mohamed Ali; Zemzemi, Lamia; Kamoun, Ines; Babba, Hamouda; Oudni-M’rad, Myriam (Frontiers in Veterinary Science, 2025)
IntroductionCystic echinococcosis (CE) is a zoonosis caused by the larval stage of the Echinococcus granulosus sensu lato (s.l.) complex. CE is globally distributed, with a particularly high prevalence in North African countries, especially Tunisia. Despite its significant public health impact and the economic burden it places on livestock production, recent data on CE prevalence in Tunisian livestock remain scarce. This study aimed to assess the prevalence of CE in livestock, investigate potential differences across host species, and identify risk factors contributing to the CE transmission dynamics.MethodsThe study was conducted in two governorates located in the North-Eastern region of Tunisia. A multidimensional approach included post-mortem inspection of slaughtered animals, fertility and viability analyses of the isolated CE cysts, and molecular genotyping of the parasite was conducted.Results and discussionA total of 21,487 animals were examined, 15.86% of the sheep and 9.57% of the cattle were infected with at least one CE cyst, with females showing higher prevalence rates. No CE cases were detected in goats or dromedaries. In all infected animals, the infection rate increased with the age of the host. CE cysts were predominantly found in both the liver and lung of the same animal in sheep and cattle. Aborted lesions were the most common stage of infection, and multiple CE cysts were frequently observed in affected animals. Fertile CE cysts were highly prevalent in both sheep and cattle, with rates increasing with host age, confirming the critical role of sheep in the parasite transmission cycle and demonstrating that cattle in Tunisia also play a significant role in the propagation of CE. Molecular analysis confirmed the predominance of the zoonotic G1 genotype of E. granulosus sensu stricto. This is particularly concerning as the G1 genotype is also the most common genotype affecting humans. This underscores a strong zoonotic potential and highlights the need for integrated control strategies. The findings emphasize the role of the livestock-dog cycle in CE transmission, posing risks to humans living near infected animals. Effective measures, including slaughter regulations, dog deworming, public education, and enhanced veterinary surveillance within a One Health approach, are essential for reducing CE’s impact on human and animal health.